Donor site scar preference in head and neck free flap reconstruction: The patient point of view - Andrea Iandelli; Francesco Mazzola; Fabrizio Di Mari; Gilda Gaglio; Giulia Bianchi; Filippo Marchi; Giovanni Zoccali; Flaminia Campo; Giampiero Parrinello; Gerardo Petruzzi; Giorgio Peretti; Raul Pellini (Oral Oncology Reports)
Background: Several free flaps are nowadays available for functional reconstruction after hemi-glossectomy in head and neck oncologic surgery. Radial forearm free flap (RFFF) and anterolateral thigh (ALT) have been played a workhorse role until recent years, when other valuable options such as Medial Sural Artery Perforator (MSAP) flap and Profunda Artery Perforator (PAP) flap demonstrated to be suitable contenders and are increasingly taken into account. This study aims to investigate the preference of the donor site in the light of esthetical and functional outcomes. Methods: The participants attended a one-to-one interview with a surgeon explaining a standardized head and neck oncological procedure requiring a soft tissue reconstruction. The donor site preference in terms of esthetical, functional and overall outcomes among these four flap options was investigated. Results: Univariable and multivariable analysis were performed comparing the donor site preference between the two most widespread free flap RFFF vs ALT. Subsequently, the analysis was performed comparing RFFF, ALT, MSAP and PAP. Conclusions: The study illustrated that a diverse group of patients exhibits similarly diverse preferences and expectations. As we observe a shift in the age distribution of patients with OSCC from the fifth-sixth decade towards the two extremes, and an increased incidence in the female population, it becomes essential to enhance reconstructive options provided to patients. This ensures that, while maintaining an equivalent functional outcome, we maximize patient satisfaction to the fullest extent possible.